STRATEGI MENGURANGI ANGKA GOLPUT PADA PILKADA KOTA BEKASI 2024 - Septianingrum, Alya; Rofieq, Ainur (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The General Elections Commission (KPU) as the organizer of the Local Election (Pilkada) has developed and prepared a strategy to reduce the number of abstentions in the 2024 Bekasi City Election. In the previous regional elections, there were still many Bekasi City people who did not exercise their voting rights (golput) and community participation had not reached the national target of 77.5%. For this reason, the Bekasi City KPU has developed a strategy so that the regional elections in 2024 will have a low abstention rate. The purpose of this study is to analyze the KPU strategy for reducing the number of abstentions in the 2024 Local Election in Bekasi City. The research methodology uses the constructivism paradigm with qualitative research methods accompanied by a case study approach. The data collection techniques are through observation, in-depth interviews, literature studies, and documentation, as well as informant retrieval by purposive sampling. The results of the study stated that the KPU strategy in reducing the number of abstentions in the 2024 regional elections was by the desired strategy consisting of targets, policies, and plans to be realized. Based on the strategy realized, the Bekasi City KPU has realized several activities, one of which is by carrying out socialization and voter education in schools. This was done to increase public awareness of the importance of participating in using their voting rights in the 2024 local elections.